HUMANIZING POLITICAL AUTHORITY IN THE MALAY WORLD: Raja Ali Haji’s Demythologization of Kingship in the Context of Asia-Pacific Islamic Political Thought - Palawa, Alimuddin Hassan (Asia-Pacific Journal on Religion and Society, 2026)
This article explores the political thought of Raja Ali Haji, a 19th-century Malay intellectual, focusing on his critique of the sacred symbolism surrounding kingship in traditional Malay-Islamic society. Drawing upon his seminal works, Thamarāt al-Muhimmah, Tuḥfat al-Nafīs, and Syair Nasehat, the study analyzes how Raja Ali Haji deconstructs the mythologization of royal authority and offers a model of leadership grounded in morality, knowledge, and historical consciousness. Central to his argument is the concept of sunnatullah—a divine law operating through history—which he employs to explain the downfall of unjust rulers and to advocate for political accountability. This paper situates Raja Ali Haji’s thought within the broader discourse of Islamic political philosophy while also contextualizing its relevance to contemporary challenges in the Asia-Pacific region, where monarchical and dynastic politics remain prominent. By foregrounding the integration of naql (revelation), aql (reason), and historical reflection, Raja Ali Haji’s political vision presents an epistemic alternative to both Western-centric political theories and locally entrenched authoritarian structures. The article argues that his humanistic and ethical approach to leadership is not only historically significant but also offers critical insights into current debates on political legitimacy, democratization, and moral governance in Southeast Asia and the wider Asia-Pacific.